ETHNOLINGUISTIC SCENARIO: THE REMAINING NATIVE LANGUAGES IN THE MUNICIPALITIES OF ATALAIA DO NORTE AND TABATINGA IN THE MICROREGION OF ALTO-SOLIMÕES, AM/BRAZIL - Macedo Ribeiro, Edinelza; Caroline Santos Alves, Júnia (Revista Gênero e Interdisciplinaridade, 2025)
The Alto Solimões microregion, located in the western part of the state of Amazonas, on the triple border between Brazil, Peru, and Colombia, is characterized by significant ethnic and linguistic diversity, consolidated over centuries of indigenous occupation. This study sought to identify, through scenario building, the future of the remaining native languages ​​in the Alto Solimões microregion, with emphasis on the municipalities of Atalaia do Norte and Tabatinga/AM. The proposal stems from the recognition of the ethnolinguistic diversity present in the region and the need to understand the possible unfolding of this diversity in the face of ongoing social, cultural, political, and educational transformations. An important finding was the existence of eleven native languages ​​that still remain in the municipalities of Atalaia do Norte and Tabatinga. It was also found that all the native languages ​​evidenced in both municipalities are active. Regarding the entry of the indigenous population into higher education, the municipality of Atalaia do Norte has reduced access for indigenous students due to geographical conditions and territorial isolation. In Tabatinga, the potential for indigenous people to access universities became evident, due to urbanization and a greater presence of universities.